Honeycomb ZIF-derived layered double hydroxide composite material as well as preparation method and application thereof
The preparation of honeycomb-like ZIF-derived layered double hydroxide composite material solves the problem of low electron conductivity and easy agglomeration and accumulation in supercapacitors, achieving high specific capacity and cyclic stability of the material, and significantly improving electrochemical performance.
Patent Information
- Application Number
- CN202311334480.0
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2023-10-16
- Publication Date
- 2025-04-18
- Estimated Expiration
- 2043-10-16
AI Technical Summary
Layered double hydroxide (LDH) has problems with low electron conductivity and easy agglomeration and accumulation in supercapacitors, resulting in limited application in practical use.
The honeycomb-like ZIF-derived layered double hydroxide composite material was prepared by ion exchange method, and ZIF-67 was etched with nickel ions to form a honeycomb-like structure assembled nanosheets, avoiding agglomeration and exposing more electrochemically active sites.
The specific surface area of the material is increased, the electrochemically active site exposure is more, and the electron and ion transmission distance is shortened, the specific capacity and cyclic stability of the electrode are improved, and the electrochemical performance is significantly improved.
Smart Images

Figure CN119852102A_ABST
Abstract
Description
Technical Field
[0001] The invention belongs to the technical field of supercapacitor energy storage, and in particular relates to a honeycomb ZIF-derived layered double hydroxide composite electrode and a preparation method and application thereof. Background Art
[0002] Environmental pollution and fossil energy depletion are two major problems facing mankind today. Vigorously developing clean and renewable energy is a hot topic in the world today. Developing supercapacitors with high conversion efficiency and long-term stability is one of the important strategies to scientifically utilize clean energy and achieve sustainable development of renewable energy to promote social development. Designing electrodes with multi-components and multi-dimensional structures is a key technology for assembling efficient supercapacitors.
[0003] Layered double hydroxide (LDH) is widely used as a supercapacitor electrode material due to its high theoretical capacity, large specific surface area, and good redox activity. However, in the process of practical application, its low electronic conductivity and easy layered aggregation and accumulation, which leads to a reduction in the number of exposed active sites and blockage of electrolyte ion transmission channels, hinder its possibility of large-scale application. Multicomponents can make full use of the synergistic effects between different components and provide multiple reversible metal ion redox pairs. Constructing a three-dimensional structure of nanosheet assembly can avoid the aggregation and accumulation of LDH, increase the specific surface area of the material, expose more electrochemical active sites, and shorten the distance of electron and ion transmission. At the same time, the honeycomb structure makes full use of the internal space of the material and the volume expansion of the buffer electrode during the charge and discharge process, effectively improving the specific capacity and cycle stability of the electrode.
[0004] Therefore, it is urgent to invent a new composite electrode material that can significantly improve the electrochemical performance of the material. Summary of the invention
[0005] Purpose of the invention: The technical problem to be solved by the present invention is to provide a new type of honeycomb structured layered double hydroxide composite material with excellent electrochemical properties.
[0006] The technical problem that the present invention also solves is to provide a method for preparing a honeycomb ZIF-derived layered double hydroxide composite material by using an ion exchange method.
[0007] The final technical problem to be solved by the present invention is to provide an application of a layered double hydroxide composite electrode material with a honeycomb structure in the preparation of a composite electrode material.
[0008] Technical solution: In order to solve the above technical problems, the present invention provides a method for preparing a honeycomb ZIF-derived layered double hydroxide composite material, comprising the following steps:
[0009] (1) quickly adding a methanol solution of dimethylimidazole to a methanol solution of nitrate, mixing by magnetic stirring, standing at room temperature, centrifuging, washing with methanol, and vacuum drying to obtain polyhedral ZIF-67;
[0010] (2) ZIF-67 and Ni(NO3)2·6H2O were dispersed in ethanol with a volume fraction of 90-95%, respectively. At a certain reaction temperature, the ZIF-67 ethanol suspension was added dropwise to the nickel nitrate ethanol solution. After the reaction, the sample was collected and washed with ethanol, and finally vacuum dried to obtain the ZIF-67@NiCo LDH honeycomb composite material.
[0011] Further research found that the honeycomb structure and high-performance composite materials can only be obtained by reacting in ethanol with a volume fraction of 90 to 95%. When ethanol with other volume fractions such as 80% is used, composite materials with other different morphologies are obtained. When the volume fraction of ethanol is greater than 95%, a hollow polyhedron structure assembled by nanosheets is obtained; when the volume fraction of ethanol is between 90 and 95%, a honeycomb structure assembled by nanosheets is obtained; when the volume fraction of ethanol is less than 90%, an irregular block material is obtained. The main reason for the different morphologies is that when the water content is low, the ion exchange rate of the sample is slow to form a nanosheet structure. As the water content increases, the ion exchange rate accelerates to form a honeycomb structure assembled by nanosheets. When the water content is greater than 10%, ion exchange only occurs on the surface of the material and the nanosheet structure cannot be obtained.
[0012] Wherein, in step (1), the concentration of the methanol solution of cobalt nitrate is 50-100 g / L, and the concentration of the methanol solution of 2-methylimidazole is 10-50 g / L.
[0013] Wherein, in step (2), the mass ratio of ZIF-67 and Ni(NO3)2·6H2O is 1:(2-3).
[0014] Wherein, the concentration of ZIF-67 in the ZIF-67 suspension in step (2) is 1-4 g / L.
[0015] Wherein, the concentration of Ni(NO3)2·6H2O in the nickel nitrate ethanol solution in step (2) is 5-15 g / L.
[0016] Wherein, the reaction temperature in step (2) is 25-35° C., and the reaction time is 1-9 hours.
[0017] The specific preparation method of the present invention is as follows:
[0018] (1) 10-50 g / L dimethylimidazole methanol solution was quickly added to 50-100 g / L cobalt nitrate methanol solution, magnetically stirred for 1 hour, allowed to stand at room temperature for 24 hours, centrifuged, washed with methanol, and vacuum dried to obtain ZIF-67 polyhedron.
[0019] (2) Disperse ZIF-67 with a concentration of 1-4 g / L in 30 ml of ethanol, dissolve Ni(NO3)2·6H2O with a relative content of 5-15 g / L in 10 ml of ethanol, and the volume fraction of ethanol used is 90%-95%. Then, add the ZIF-67 dispersion to the Ni(NO3)2·6H2O solution under stirring, stir and react at 25-35°C for 1-9 hours, collect the sample after the reaction, wash it with ethanol, and vacuum dry it for 12 hours to obtain a ZIF-67@NiCo LDH honeycomb composite material.
[0020] (3) The ZIF-67@NiCo LDH honeycomb composite material was uniformly mixed with polytetrafluoroethylene and acetylene black in a mass ratio of 8:1:1 to form a slurry, which was coated on the pretreated nickel foam and used as the working electrode of the supercapacitor. The platinum sheet was used as the counter electrode, mercuric oxide was used as the reference electrode, and potassium hydroxide was used as the electrolyte to test the supercapacitor electrode performance.
[0021] The present invention also includes a ZIF-67@NiCo LDH honeycomb composite material prepared by the preparation method.
[0022] The present invention also includes the application of the ZIF-67@NiCo LDH honeycomb composite material in the preparation of a composite electrode.
[0023] The preparation of the composite electrode includes: uniformly mixing the ZIF-67@NiCo LDH honeycomb composite material with polytetrafluoroethylene and acetylene black to form a slurry, and coating the slurry on the pretreated nickel foam. The loading amount of the slurry is 0.8-1.5 mg / cm 2 .
[0024] The present invention also includes a ZIF-67@NiCo LDH composite electrode, wherein the composite electrode includes the ZIF-67@NiCo LDH honeycomb composite material.
[0025] The present invention is carried out in an environment of potassium hydroxide electrolyte during electrochemical testing, wherein the concentration of the potassium hydroxide electrolyte is 2-6 mol / L, the prepared composite electrode is used as a working electrode, a platinum sheet is used as a counter electrode, and mercury / mercuric oxide is used as a reference electrode to form a three-electrode system for electrochemical testing.
[0026] Reaction mechanism of the present invention: The present invention etches ZIF-67 with nickel ions, and obtains the ZIF-67@NiCo LDH honeycomb structure derived from ZIF in situ by controlling the etching time, etching temperature and water content of the solvent. Specifically, when the volume fraction of ethanol is 90-95%, a honeycomb structure assembled by nanosheets is obtained; the honeycomb structure assembled by nanosheets avoids the agglomeration and accumulation of LDH, increases the specific surface area of the material, can expose more electrochemical active sites, and shorten the distance of electron and ion transmission. At the same time, the honeycomb structure makes full use of the internal space of the material and the volume expansion of the buffer electrode during the charging and discharging process, effectively improving the specific capacity and cycle stability of the electrode. Therefore, the material can give full play to the synergistic effect between different materials and improve the specific capacity of the electrode. The composite material prepared by the present invention is a honeycomb structure, which is assembled from nanosheet structures. The honeycomb structure of the present invention can increase the contact area between the electrode and the electrolyte, increase the active sites of the electrochemical reaction, increase the electron transmission channel and improve the conductivity, and can solve the problem of easy agglomeration and accumulation of layered double hydroxides and structural collapse during the cycle, thereby improving the cycle performance of the electrode material and thus improving the electrochemical performance of the electrode material.
[0027] Beneficial effects: Compared with the prior art, the present invention gives full play to the synergistic effect between different materials and improves the specific capacity of the electrode. The present invention directly obtains the honeycomb ZIF-derived layered double hydroxide composite material by ion exchange. This method is simple to operate, has good reproducibility, and is easy to scale up. The electrode prepared from the ZIF-67@NiCo LDH honeycomb composite material prepared by the present invention has excellent electrochemical properties. BRIEF DESCRIPTION OF THE DRAWINGS
[0028] Figure 1 Scanning electron microscope image of the sample of Example 3;
[0029] Figure 2 The charge and discharge curve of the sample of Example 3;
[0030] Figure 3 Scanning electron microscope image of the sample of Comparative Example 1. DETAILED DESCRIPTION
[0031] In order to better understand the present invention, the present invention is further illustrated by the following embodiments, but the content of the present invention is not limited to the following examples.
[0032] Example 1 Preparation of ZIF-67@NiCo LDH and its performance test
[0033] 1. Preparation of ZIF-67@NiCo LDH
[0034] (1) 95 ml of a 20 g / L methanol solution of dimethylimidazole was quickly added to 45 ml of a 50 g / L methanol solution of cobalt nitrate, and the mixture was stirred magnetically for 1 hour, allowed to stand at room temperature for 24 hours, centrifuged, washed with methanol, and vacuum dried to obtain ZIF-67 polyhedron.
[0035] (2) Disperse 1 g / L ZIF-67 in 30 ml ethanol and dissolve 6 g / L Ni(NO3)2·6H2O in 10 ml ethanol, with the volume fraction of ethanol used being 90%. Then, add the ZIF-67 dispersion to the Ni(NO3)2·6H2O solution under stirring, and stir at 30°C for 3 hours. After the reaction, collect the sample, wash it with ethanol, and vacuum dry it for 12 hours to obtain the ZIF-67@NiCo LDH honeycomb composite material.
[0036] 2. Preparation of ZIF-67@NiCo LDH honeycomb composite electrode materials
[0037] The ZIF-67@NiCo LDH honeycomb composite material was uniformly mixed with polytetrafluoroethylene and acetylene black at a mass ratio of 8:1:1 to form a slurry. The slurry was heated to 1 mg / cm 2 It is coated on the pretreated nickel foam as the working electrode of the supercapacitor, the platinum sheet is the counter electrode, the mercuric oxide is the reference electrode, and the electrolyte is 2 mol / L potassium hydroxide solution.
[0038] 3. Performance testing
[0039] The ZIF-67@NiCo LDH honeycomb composite electrode material was tested for supercapacitor electrode performance. At 1 ampere / gram, the specific capacity of the ZIF-67@NiCo LDH honeycomb composite electrode material was as high as 1620 farads / gram, and the capacitance retention rate was 68% when the current density was 10 amperes / gram. When the current density was 10 amperes / gram, the capacitance retention rate of the ZIF-67@NiCoLDH honeycomb composite material was 73% after 10,000 cycles.
[0040] Example 2 Preparation and performance testing of ZIF-67@NiCo LDH honeycomb composite electrode material
[0041] 1. Preparation of ZIF-67@NiCo LDH
[0042] (1) 95 ml of 30 g / L dimethylimidazole methanol solution was quickly added to 45 ml of 65 g / L cobalt nitrate methanol solution, magnetically stirred for 1 hour, allowed to stand at room temperature for 24 hours, centrifuged, washed with methanol, and vacuum dried to obtain ZIF-67 polyhedron.
[0043] (2) Disperse 3 g / L ZIF-67 in 30 ml ethanol, dissolve 10 g / L Ni(NO3)2·6H2O in 10 ml ethanol, and the volume fraction of ethanol used is 95%. Then, add the ZIF-67 dispersion to the Ni(NO3)2·6H2O solution under stirring, and stir at 30°C for 4 hours. After the reaction, collect the sample, wash it with ethanol, and vacuum dry it for 12 hours to obtain the ZIF-67@NiCo LDH honeycomb composite material.
[0044] 2. Preparation of ZIF-67@NiCo LDH honeycomb composite electrode materials
[0045] The ZIF-67@NiCo LDH honeycomb composite material was uniformly mixed with polytetrafluoroethylene and acetylene black at a mass ratio of 8:1:1 to form a slurry. The slurry was heated to 1 mg / cm 2 It is coated on the pretreated nickel foam as the working electrode of the supercapacitor, the platinum sheet is the counter electrode, the mercuric oxide is the reference electrode, and the electrolyte is a 3 mol / L potassium hydroxide solution.
[0046] 3. Performance testing
[0047] The ZIF-67@NiCo LDH honeycomb composite electrode material was tested for supercapacitor electrode performance. At 1 ampere / gram, the specific capacity of the ZIF-67@NiCo LDH honeycomb composite electrode material was as high as 1680 farads / gram, and the capacitance retention rate was 70% when the current density was 10 amperes / gram. When the current density was 10 amperes / gram, the capacitance retention rate of the ZIF-67@NiCoLDH honeycomb composite material was 75% after 10,000 cycles.
[0048] Example 3 Preparation and performance testing of ZIF-67@NiCo LDH
[0049] 1. Preparation of ZIF-67@NiCo LDH
[0050] (1) 95 ml of 40 g / L dimethylimidazole methanol solution was quickly added to 45 ml of 70 g / L cobalt nitrate methanol solution, magnetically stirred for 1 hour, allowed to stand at room temperature for 24 hours, centrifuged, washed with methanol, and vacuum dried to obtain ZIF-67 polyhedron.
[0051] (2) Disperse 2 g / L ZIF-67 in 30 ml ethanol, dissolve 14 g / L Ni(NO3)2·6H2O in 10 ml ethanol, and the volume fraction of ethanol used is 95%. Then, add the ZIF-67 dispersion to the Ni(NO3)2·6H2O solution under stirring, and stir at 30°C for 5 hours. After the reaction, collect the sample, wash it with ethanol, and vacuum dry it for 12 hours to obtain the ZIF-67@NiCo LDH honeycomb composite material.
[0052] 2. Preparation of ZIF-67@NiCo LDH honeycomb composite electrode materials
[0053] The ZIF-67@NiCo LDH honeycomb composite material was uniformly mixed with polytetrafluoroethylene and acetylene black at a mass ratio of 8:1:1 to form a slurry. The slurry was heated to 1 mg / cm 2 It is coated on the pretreated nickel foam as the working electrode of the supercapacitor, the platinum sheet is the counter electrode, the mercuric oxide is the reference electrode, and the electrolyte is 6 mol / L potassium hydroxide solution.
[0054] 3. Performance testing
[0055] The ZIF-67@NiCo LDH honeycomb composite electrode material was tested for supercapacitor electrode performance. At 1 ampere / gram, the specific capacity of the ZIF-67@NiCo LDH honeycomb composite electrode material was as high as 1730 farads / gram, and the capacitance retention rate was 76% when the current density was 10 amperes / gram. When the current density was 10 amperes / gram, the capacitance retention rate of the ZIF-67@NiCoLDH honeycomb composite material was 82% after 10,000 cycles.
[0056] Example 4 Preparation and performance testing of ZIF-67@NiCo LDH
[0057] 1. Preparation of ZIF-67@NiCo LDH
[0058] (1) 95 ml of 50 g / L dimethylimidazole methanol solution was quickly added to 45 ml of 90 g / L cobalt nitrate methanol solution, magnetically stirred for 1 hour, allowed to stand at room temperature for 24 hours, centrifuged, washed with methanol, and vacuum dried to obtain ZIF-67 polyhedron.
[0059] (2) Disperse 4 g / L ZIF-67 in 30 ml ethanol, dissolve 14 g / L Ni(NO3)2·6H2O in 10 ml ethanol, and the volume fraction of ethanol used is 95%. Then, add the ZIF-67 dispersion to the Ni(NO3)2·6H2O solution under stirring, and stir at 30°C for 6 hours. After the reaction, collect the sample, wash it with ethanol, and vacuum dry it for 12 hours to obtain the ZIF-67@NiCo LDH honeycomb composite material.
[0060] 2. Preparation of ZIF-67@NiCo LDH honeycomb composite electrode materials
[0061] The ZIF-67@NiCo LDH honeycomb composite material was uniformly mixed with polytetrafluoroethylene and acetylene black in a mass ratio of 8:1:1 to form a slurry, which was coated on the pretreated nickel foam as the working electrode of the supercapacitor, the platinum sheet as the counter electrode, mercuric oxide as the reference electrode, and the electrolyte was 6 mol / L potassium hydroxide solution.
[0062] 3. Performance testing
[0063] The ZIF-67@NiCo LDH honeycomb composite electrode material was tested for supercapacitor electrode performance. At 1 ampere / gram, the specific capacity of the ZIF-67@NiCo LDH honeycomb composite electrode material was as high as 1700 farads / gram, and the capacitance retention rate was 75% when the current density was 10 amperes / gram. When the current density was 10 amperes / gram, the capacitance retention rate of the ZIF-67@NiCoLDH honeycomb composite material was 80% after 10,000 cycles.
[0064] Comparative Example
[0065] 1. Preparation of ZIF-67@NiCo LDH bulk materials
[0066] (1) 95 ml of 40 g / L dimethylimidazole methanol solution was quickly added to 45 ml of 70 g / L cobalt nitrate methanol solution, magnetically stirred for 1 hour, allowed to stand at room temperature for 24 hours, centrifuged, washed with methanol, and vacuum dried to obtain ZIF-67 polyhedron.
[0067] (2) Disperse 2 g / L ZIF-67 in 30 ml ethanol, dissolve 14 g / L Ni(NO3)2·6H2O in 10 ml ethanol, and the volume fraction of ethanol used is 80%. Then, add the ZIF-67 dispersion to the Ni(NO3)2·6H2O solution under stirring, and stir at 30°C for 5 hours. After the reaction, collect the sample, wash it with ethanol, and vacuum dry it for 12 hours to obtain ZIF-67@NiCo LDH bulk material.
[0068] 2. Preparation of ZIF-67@NiCo LDH electrode materials
[0069] The ZIF-67@NiCo LDH bulk composite material was uniformly mixed with polytetrafluoroethylene and acetylene black at a mass ratio of 8:1:1 to form a slurry. The slurry was heated to 1 mg / cm 2 It is coated on the pretreated nickel foam as the working electrode of the supercapacitor, the platinum sheet is the counter electrode, the mercuric oxide is the reference electrode, and the electrolyte is 6 mol / L potassium hydroxide solution.
[0070] 3. Performance testing
[0071] The ZIF-67@NiCo LDH electrode material was tested for supercapacitor electrode performance. At 1 ampere / gram, the specific capacity of the ZIF-67@NiCo LDH electrode material was about 800 farads / gram, and the capacitance retention rate was 50% when the current density was 10 amperes / gram. When the current density was 10 amperes / gram, the capacitance retention rate of the ZIF-67@NiCo LDH bulk composite material was 40% after 10,000 cycles.
Claims
1. A method for preparing a honeycomb ZIF-derived layered double hydroxide composite material, characterized in that: The following steps are involved: (1) The methanol solution of dimethylimidazole was quickly added to the methanol solution of nitrate, mixed by magnetic stirring, allowed to stand at room temperature, centrifuged, washed with methanol, and vacuum dried to obtain polyhedral ZIF-67; (2) ZIF-67 and Ni(NO3)2∙6H2O were dispersed in ethanol with a volume fraction of 90-95%, respectively. At a certain reaction temperature, the ZIF-67 ethanol suspension was added dropwise to the nickel nitrate ethanol solution. After the reaction, the sample was collected and washed with ethanol, and finally vacuum dried to obtain the ZIF-67@NiCo LDH honeycomb composite material.
2. The method for preparing the honeycomb ZIF-derived layered double hydroxide composite material according to claim 1, characterized in that: In step (1), the concentration of the methanol solution of cobalt nitrate is 50-100 g / L, and the concentration of the methanol solution of 2-methylimidazole is 10-50 g / L.
3. The method for preparing the honeycomb ZIF-derived layered double hydroxide composite material according to claim 1, characterized in that: In step (2), the mass ratio of ZIF-67 and Ni(NO3)2∙6H2O is 1:(2-3).
4. The method for preparing the honeycomb ZIF-derived layered double hydroxide composite material according to claim 1, characterized in that: The concentration of ZIF-67 in the ZIF-67 suspension in step (2) is 1-4 g / L.
5. The method for preparing the honeycomb ZIF-derived layered double hydroxide composite material according to claim 1, characterized in that: The concentration of Ni(NO3)2∙6H2O in the nickel nitrate ethanol solution in step (2) is 5-15 g / L.
6. The method for preparing the honeycomb ZIF-derived layered double hydroxide composite material according to claim 1, characterized in that: The reaction temperature in step (2) is 25-35°C and the reaction time is 1-9 hours.
7. The ZIF-67@NiCo LDH honeycomb composite material prepared by the preparation method according to any one of claims 1 to 7.
8. Use of the ZIF-67@NiCo LDH honeycomb composite material according to claim 8 in preparing a composite electrode.
9. The use according to claim 8, characterized in that: The preparation of the composite electrode comprises: uniformly mixing the ZIF-67@NiCo LDH honeycomb composite material with polytetrafluoroethylene and acetylene black to form a slurry, and coating the slurry on the pretreated nickel foam, wherein the loading amount of the slurry is 0.8-1.5 mg / cm 2 .
10. A ZIF-67@NiCo LDH composite electrode, characterized in that: The composite electrode comprises the ZIF-67@NiCo LDH honeycomb composite material as described in claim 8.
Citation Information
Patent Citations
A rapid preparation method of NiCo-LDH electrode material for supercapacitor
CN108987121A
Co2P@Ni2P / CC honeycomb nanosheet composite material based on ZIF67 derivation and application thereof
CN112259379A
Nickel-cobalt bimetallic layered hydroxide material with multilevel structure and preparation method of nickel-cobalt bimetallic layered hydroxide material
CN113096965A